A fluctuating plume model for pollutants dispersion with chemical reactions. (13th October 2012) - Ferrero, Enrico; Mortarini, Luca; Alessandrini, Stefano; Lacagnina, Carlo
A fluctuating plume model for pollutant dispersion is developed. The model is able to include chemical reactions, accounting for segregation. The model is tested against measured data in wind tunnel experiment, where NO is emitted from a source in an environment of ozone. The results are presented in terms of the plume centre line dispersion and cross sections at different distances. It is shown that the agreement between predicted and measured values is satisfactory, notwithstanding the limitations due to the one-dimensional scheme adopted for the model.